Environment, corporate entrepreneurship, and financial performance: A taxonomic approach - Zahra, Shaker A. (Journal of Business Venturing, 1993)
This study examined the association between a firm's external environment, corporate entrepreneurship, and financial performance. The study emphasized three propositions: (1) perceived—rather than objective-characteristics of the environment significantly influenced entrepreneurship activities; (2) a multidimensional definition of a firm's environment was essential to unravel the interplay between the environment, orporate entrepreneurship activities, and financial performance; and (3) a taxonomic approach had the advantage of accounting for the interrelationships among the dimensions of the environment in classifying firms. Using data from 102 companies in six4-digit industrial classification codes (SIC),cluster analysis was used to distinguish four environmental settings: “dynamic growth,” “hostile and rivalrous but technologically rich,” “hospitable, product-driven growth,” and “static and impoverished” environments. These four environments varied in their characteristics. The four empirically derived environment clusters were then used to examine variations in corporate entrepreneurship—operationalized as corporate innovation and venturing, and corporate renewal activities. The first dimension—corporate innovation and venturing—had four components: new business creation, new product introduction, percent of revenue from new products, and technological entrepreneurship. The renewal dimension had three components: mission reformulation, reorganization, and system-wide change. The data were used to test six hypotheses: 1.H1: In dynamic or growth environments, companies will emphasize new business creation and innovation.2.H2: Environmental hostility is positively associated with the redefinition of business through venturing activities.3.H3: Hospitable business environments are positively associated with business venturing and renewal activities.4.H4: Static environments are inversely associated with corporate venturing and renewal activities.5.H5: Corporate entrepreneurship activities are positively associated with company financial performance.6.H6: Corporate entrepreneurship activities emphasised in HI through H4 will be significantly and positively associated with company financial performance in their respective environmental clusters. The results provided general support for the six hypotheses. They showed that: (1) each environmental cluster had a distinct combination of activities relating to corporate innovation and venturing, and renewal; (2) corporate entrepreneurship activities varied in their associations with measures of company growth and profitability; and (3) the associations between corporate entrepreneurship and company financial performance varied among the four environment clusters. The results from this study can help executives in selecting specific entrepreneurial activities that match the demands of success in their business environment to improve their company's performance.